Normal eye fundus in dog and cat - LIAPIS (Ι. Κ. ΛΙΑΠΗΣ), I. K. (Journal of the Hellenic Veterinary Medical Society, 2018)
The term eye fundus is clinical and indicates the posterior part of eye globe, which is visible during ophthalmoscopy. In dogs mostly, but also in cats, eye fundus presents an important variability. All globe layers (retina,chorioid and sclera tuniques) could be visualized during ophthalmoscopy. Main anatomic components of fundus image are: a)Retinal vessels,b)The optic disc, c)The retinal pigment epithelium (invisible in albinoid animals) and d) The tapetum lucidum which gives the metallic nuance of fundus and can be hypoplastic or missing. The normalappearance of fundus is completed beyond the 16th week after birth. Until then the image is unclear. Careful estimation of numerous variations of normal eye fundus image is necessary, because plenty of them can be confused with pathologic situations.